Conceptualising the process of e-governance: The e-seva experience in Hyderabad - Satish Babu, D.R.; Prasad, Sheela (2009)
As a part of the reform agenda, the e-governance project called `e-seva was first set up in Hyderabad in 1999. This project seeks to provide smart and good governance, in tune with the principles of new public management and the changing nature of the state. The e-seva aims to cover electronic service as `one-stop-shop' between G2G, G2C, G2B in an effective, efficient, convenient, equitable, cost-effective manner. This article analyses the citizens' positive response to the application of `e-services' in e-seva centres in providing effective governance in Hyderabad region. The survey based on a study of selected e-seva centres in Hyderabad, shows that compared to the earlier practices e-services are more reliable, citizen-centred and reduce corruption. - Reproduced.
Keywords: E governance - India - Andhra Pradesh; E governance